2016
DOI: 10.1186/s40900-016-0016-0
|View full text |Cite
|
Sign up to set email alerts
|

Older people’s priorities in health and social care research and practice: a public engagement workshop

Abstract: Plain English SummaryA one day public engagement workshop was held to focus on the priorities of older people about research and practice in health and social care. Seventy-five older people from the general public and a variety of backgrounds attended this event to share their views and discuss what should be prioritised. The main aim of this workshop was to identify and prioritise issues that are important to older people that would benefit from further research, as well as create an environment for older pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…Within the broad themes of mind health and social well‐being, sub‐themes emerged—social isolation/loneliness, devaluing of older adults and stigma related to ageing. These findings are supported by those of Alsaeed and colleagues, who conducted a one‐day public engagement workshop to determine the priorities of older people for research and found loneliness, isolation and negative perceptions of older adults to be key research priorities . For participants in our roadshows, social isolation and loneliness were inextricably linked to issues around housing and the environment.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Within the broad themes of mind health and social well‐being, sub‐themes emerged—social isolation/loneliness, devaluing of older adults and stigma related to ageing. These findings are supported by those of Alsaeed and colleagues, who conducted a one‐day public engagement workshop to determine the priorities of older people for research and found loneliness, isolation and negative perceptions of older adults to be key research priorities . For participants in our roadshows, social isolation and loneliness were inextricably linked to issues around housing and the environment.…”
Section: Discussionsupporting
confidence: 74%
“…Research priority setting is a pivotal function of national health research systems, guiding investment in health care and health‐care research, and channelling resource allocation to areas of highest research priority . Ensuring broad stakeholder engagement was a key focus of this prioritisation exercise, as few research prioritisation exercises have a broad degree of involvement with key stakeholders …”
Section: Introductionmentioning
confidence: 99%
“…1 The research prioritisation process views on key topics for research exploring the experience of living with and beyond cancer with comorbid illness. The workshop was modelled on the consultation approach in the first round of the Delphi process [28], and is a similar approach to that used previously [28,34]. Relevant quality markers developed as part of the Delphi and CHNRI methods informed the planning and implementation of the workshop, such as adequate planning and preparation, inclusiveness of relevant stakeholders and transparency in reporting [29,35].…”
Section: Patient and Carer Consultation Eventmentioning
confidence: 99%
“…One of the reasons could be the reluctance to visit a health care facility in India, another could be stigma attached to the disease. 18 A study conducted by Raffetti et al showed that 75% of elderly population were late presenter. 19 Much attention was not given towards elderly PLHIV in the past because their number was less.…”
Section: Discussionmentioning
confidence: 99%